Directly Assembled 3D Molybdenum Disulfide on Silicon Wafer for Efficient Photoelectrochemical Water Reduction. (15th January 2018) - Andoshe, Dinsefa Mensur; Jin, Gangtae; Lee, Chang‐Soo; Kim, Changyeon; Kwon, Ki Chang; Choi, Seokhoon; Sohn, Woonbae; Moon, Cheon Woo; Lee, Seung Hee; Suh, Jun Min; Kang, Sungwoo; Park, Jaehyun; et al.
Abstract: MoS2 composed of earth‐abundant elements is considered as a promising hydrogen evolution reaction (HER) catalyst for p‐type Si photocathode owing to its appropriate hydrogen adsorption free energy for the edge sites and high photochemical stability in acidic electrolytes. However, the direct synthesis of uniform and atomically thin MoS2 on Si by usual chemical vapor deposition techniques remains challenging because of the weak van der Waals interaction between Si and MoS2 . Herein, by controlling the gas phase kinetics during metal–organic chemical vapor deposition, wafer‐scale direct synthesis of 3D MoS2 films on TiO2 ‐coated p‐type Si substrates is demonstrated. The 3D MoS2 layer with a number of edge sites exposed to ambient substantially reduces the HER overpotential of Si photocathode and simultaneously increases the saturation current density due to the antireflection effect. Directly grown 3D MoS2 thin films are stable under extended water reduction duration. The strategy paves the way for efficient assembly of transition metal disulfide HER catalysts on the p‐type photocathode. Abstract : High‐photoelectrochemical performance of TiO2 /p‐Si photocathodes is demonstrated by incorporating directly grown 3D MoS2 hydrogen evolution reaction (HER) catalysts with high density of exposed edge‐sites and nanoscale grain boundaries. The lengthy MoS2 transfer process is bypassed and few layers of 3D MoS2 are directly grown on p‐Si‐based electrode, and this solves the bottleneck of transferred MoS2 HER catalyst on p‐type silicon substrate.